Collected stories : - McCullers, Carson (Houghton Mifflin, 1987)
Carson McCullers--novelist, dramatist, poet--was at the peak of her powers as a writer of short fiction. Here are nineteen stories that explore her signature themes: wounded adolescence, loneliness in marriage, and the tragicomedy of life in the South. Here too are "The Member of the Wedding" and "The Ballad of the Sad Cafe," novellas that Tennessee Williams judged to be "assuredly among the masterpieces of our language." (A Mariner Reissue)